The Fantastic Four Ps of Islamic Digital Marketing in Boosting the Asnaf Economy - Mohd Hajar, Muhammad Nurfiqri; Abdul Rahim, Razinda Tasnim; Bistaman, Izwan Nurli Mat (Information Management and Business Review, 2025)
In Perlis, initiatives to support asnafpreneurs lead to empowering these individuals through entrepreneurship, fostering self-reliance and economic growth. Programs may include training, micro-financing, and resources to help asnafpreneurs start and sustain their businesses. On the other hand, digital marketing encompasses various online strategies to promote products or services. For asnafpreneurs in Perlis, digital marketing can be a powerful tool to reach wider audiences, build brand awareness, and drive sales. In addition, the added Islamic value in digital marketing is expected to contribute to promoting Visit Perlis 2024. Therefore, this study aims to foresee the marketing mix elements 4Ps- Product, Price, Place, and Promotion with Islamic value integration in boosting the asnafpreneurs economy. In addition, this study employed a qualitative method. The data collected was among asnafpreneurs during a business workshop organized by Majlis Agama Islam Perlis (MAIPs). Four elements of the marketing mix and the integration of Islamic values are implemented to fill out the structured interview with five asnafpreneurs. Moreover, based on the findings, this study highlights asnafpreneurs’ awareness of Islamic digital marketing. The impacts of Islamic digital marketing are analyzed and discussed in the concluding section. Additionally, several limitations are acknowledged, and recommendations for future research are provided.